Van privileges tot republiek: Evolutie van de taal van de Opstand. Een woordenboek / From the Privileges to the Republic: the Evolution of the Language of the Dutch Revolt. A Dictionary - Szmytka, Rafał (Werkwinkel, 2015)
The second half of the 16th century is regarded as the decisive moment in the history of the Low Countries. The politics of religious intolerance and financial oppression practiced by the Habsburg governors resulted in protests and, finally, in the open revolt of the Provinces under the leadership of the princes of Orange and Nassau. The aim of this work is to follow and reconstruct the ideas of political thought accompanying the events leading to the rise of a new state. In the dicussed state forming process the main emphasis was put on the issues of freedom, states, and sovereignty, as well as on the concept of the possibility of dismissing the obedience inherited from the medieval privileges. These concepts and terms created a special sort of dictionary of the Dutch political thought.